(3LeY GdahGFO GdefJNHI GdUMjMI ef GdNhGU GdeLQHIs - (3nCoHh GdnYdGA GdEnjGOj , RgQ Hf YHO Gdedc Hf eMeO Hf eQhGf GHf RgQ, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3LeY ddahGFO GdefJNHI dcejGS , gQeS HGH GdCda EfSGf TYQ GdEfSGf hEf hVY HQCS fGje RGO ai fheg s
(3BNQgG (B:s
(3MQa GdjGA jHQL gh Tcd Ydi gjFI GdEfSGf ai HdGO GdJQc jchf JMJ GdCQV hdG jbdb GdG GdcdH hQHeG eGJ hbJ bdYg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1538) s
Keywords: (3GdWHs